Transmission of SARS-CoV-2 on mink farms between humans and mink and back to humans - Oude Munnink, Bas B.; Sikkema, Reina S.; Nieuwenhuijse, David F.; Molenaar, Robert Jan; Munger, Emmanuelle; Molenkamp, Richard; van der Spek, Arco; Tolsma, Paulien; Rietveld, Ariene; Brouwer, Miranda; Bouwmeester-Vincken, Noortje; Harders, Frank; et al. (Science (American Association for the Advancement of Science), 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a zoonotic virus—one that spilled over from another species to infect and transmit among humans. We know that humans can infect other animals with SARS-CoV-2, such as domestic cats and even tigers in zoos. Oude Munnink et al. used whole-genome sequencing to show that SARS-CoV-2 infections were rife among mink farms in the southeastern Netherlands, all of which are destined to be closed by March 2021 (see the Perspective by Zhou and Shi). Toward the end of June 2020, 68% of mink farm workers tested positive for the virus or had antibodies to SARS-CoV-2. These large clusters of infection were initiated by human COVID-19 cases with viruses that bear the D614G mutation. Sequencing has subsequently shown that mink-to-human transmission also occurred. More work must be done to understand whether there is a risk that mustelids may become a reservoir for SARS-CoV-2. Science , this issue p. 172 ; see also p. 120 Genetic evidence indicates that SARS-CoV-2 transmission occurred from humans to mink as well as from mink to humans on farms in the Netherlands. Animal experiments have shown that nonhuman primates, cats, ferrets, hamsters, rabbits, and bats can be infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In addition, SARS-CoV-2 RNA has been detected in felids, mink, and dogs in the field. Here, we describe an in-depth investigation using whole-genome sequencing of outbreaks on 16 mink farms and the humans living or working on these farms. We conclude that the virus was initially introduced by humans and has since evolved, most likely reflecting widespread circulation among mink in the beginning of the infection period, several weeks before detection. Despite enhanced biosecurity, early warning surveillance, and immediate culling of animals in affected farms, transmission occurred between mink farms in three large transmission clusters with unknown modes of transmission. Of the tested mink farm residents, employees, and/or individuals with whom they had been in contact, 68% had evidence of SARS-CoV-2 infection. Individuals for which whole genomes were available were shown to have been infected with strains with an animal sequence signature, providing evidence of animal-to-human transmission of SARS-CoV-2 within mink farms.